Experimental study of delivery of humidified‐warm carbon dioxide during open abdominal surgery. Issue 5 (28th November 2017) - Carpinteri, S.; Sampurno, S.; Malaterre, J.; Millen, R.; Dean, M.; Kong, J.; Chittleborough, T.; Heriot, A.; Lynch, A. C.; Ramsay, R. G.
Abstract : Background: The aim of this study was to monitor the effect of humidified‐warm carbon dioxide (HWCO2 ) delivered into the open abdomen of mice, simulating laparotomy. Methods: Mice were anaesthetized, ventilated and subjected to an abdominal incision followed by wound retraction. In the experimental group, a diffuser device was used to deliver HWCO2 ; the control group was exposed to passive air flow. In each group of mice, surgical damage was produced on one side of the peritoneal wall. Vital signs and core temperature were monitored throughout the 1‐h procedure. The peritoneum was closed and mice were allowed to recover for 24 h or 10 days. Tumour cells were delivered into half of the mice in each cohort. Tissue was then examined using scanning electron microscopy and immunohistochemistry. Results: Passive air flow generated ultrastructural damage including mesothelial cell bulging/retraction and loss of microvilli, as assessed at 24 h. Evidence of surgical damage was still measurable on day 10. HWCO2 maintained normothermia, whereas open surgery alone led to hypothermia. The degree of tissue damage was significantly reduced by HWCO2 compared with that in controls. Peritoneal expression of hypoxia inducible factor 1α and vascular endothelial growth factor A was lowered by HWCO2 . These effects were also evident at the surgical damage sites, where protection from tissue trauma extended to 10 days. HWCO2 did not reduce tumorigenesis in surgically damaged sites compared with passive air flow. Conclusion: HWCO2 diffusion into the abdomen in the context of open surgery afforded tissue protection and accelerated tissue repair in mice, while preserving normothermia. Surgical relevance Damage to the peritoneum always occurs during open abdominal surgery, by exposure to desiccating air and by mechanical trauma/damage owing to the surgical intervention. Previous experimental studies showed that humidified‐warm carbon dioxide (HWCO2 ) reduced peritoneal damage during laparoscopic insufflation. Additionally, this intervention decreased experimental peritoneal carcinomatosis compared with the use of conventional dry‐cold carbon dioxide. In the present experimental study, the simple delivery of HWCO2 into the open abdomen reduced the amount of cellular damage and inflammation, and accelerated tissue repair. Sites of surgical intervention serve as ideal locations for cancer cell adhesion and subsequent tumour formation, but this was not changed measurably by the delivery of HWCO2 . Abstract : Reduced tissue injury